Design logos and trademarks as an innovative element in the expression of the identity of Saudi society: تصميم الشعارات والعلامات التجارية كعنصر ابداعي في التعبير عن هوية المجتمع السعودي - Abdul Majid Mahmoud Sabbagh (Journal of engineering sciences and information technology, 2017)
The success of the logos of the institutions depends to a great extent on the achievement of its functional and aesthetic goals, but to be a rich resource that emphasizes its nationality and identity to reach the summit. The commercial, cultural and social institutions in the Kingdom are a source of all directions in all spheres of life. All intellectual, scientific, And religious as it is in this course and is characterized by being an elite elite of the chosen elite of the people of the homeland, or rather this is assumed, as it is assumed to take the hand of the nation to the horizons of visions of the future and open the reins of what is closed from the doors of hope and promoted by the Renaissance in all M The mechanisms of life are both cognitive and practical. They open the way to the mind and pave the way for the workers to enlighten them and raise the level of the living, scientific, developmental and civilized nation. Through these overlapping and complex tasks, we realize the importance of the vision of these institutions. It is necessary to study the graphic elements used in the design of signs and logos that express the identity which is the visual concept of visual and invisible forms, which expresses the behavior of society from the economic, political and social aspects Yeh